An efficient hybrid method to produce high-resolution large-volume dark matter simulations for semi-analytic models of reionization. Issue 1 (22nd October 2020) - Qiu, Yisheng; Mutch, Simon J; Elahi, Pascal J; Poulton, Rhys J J; Power, Chris; Wyithe, J Stuart B
ABSTRACT: Resolving faint galaxies in large volumes is critical for accurate cosmic reionization simulations. While less demanding than hydrodynamical simulations, semi-analytic reionization models still require very large N -body simulations in order to resolve the atomic cooling limit across the whole reionization history within box sizes 100 h^-1 Mpc . To facilitate this, we extend the mass resolution of N -body simulations using a Monte Carlo algorithm. We also propose a method to evolve positions of Monte Carlo haloes, which can be an input for semi-analytic reionization models. To illustrate, we present an extended halo catalogue that reaches a mass resolution of M_halo = 3.2 × 10^7 h^-1 M_ in a 105 h^-1 Mpc box, equivalent to an N -body simulation with ∼6800 3 particles. The resulting halo mass function agrees with smaller volume N -body simulations with higher resolution. Our results also produce consistent two-point correlation functions with analytic halo bias predictions. The extended halo catalogues are applied to the meraxes semi-analytic reionization model, which improves the predictions on stellar mass functions, star formation rate densities, and volume-weighted neutral fractions. Comparison of high-resolution large-volume simulations with both small-volume and low-resolution simulations confirms that both low-resolution and small-volume simulations lead to reionization ending too rapidly. Lingering discrepancies between the star formation rate functions predicted with and without our extensions can be traced to the uncertain contribution of satellite galaxies.